Translation and validation of the German version of the Systemic Inventory of Change - Brendel, Annina; Hartmann, Mechthild; Haun, Markus W.; Pinsof, William M.; Wild, Beate (Frontiers in Psychiatry, 2026)
Background and aimThe Systemic Therapy Inventory of Change (STIC) is designed to measure changes in family, couple, and individual therapy from a multisystemic and multidimensional perspective. The aim of the present study was to translate the English version of the STIC into German and to evaluate the psychometric properties of the German version in a clinical sample of 309 patients starting outpatient psychotherapy covered by the German Statutory Health Insurance.MethodsPatients were recruited between July 2023 and November 2024 at Heidelberg Institute for Psychotherapy (HIP) of the University Hospital Heidelberg. In addition to the STIC, several other questionnaires were completed by the participants, including the Patient Health Questionnaire (PHQ-9), Childhood Trauma Questionnaire (CTQ), Experience in Close Relationships (ECR-RD-8), and the Systemic Clinical Outcome and Routine Evaluation (SCORE-15). Pearson correlation coefficients were calculated between the STIC subscales and the corresponding criterion measures.ResultsSignificant correlations with various outcome measures between 0.26 and 0.81 demonstrated the construct validity of the German version of the STIC. Multiple linear regression analyses showed that higher scores on the subscale IPS (Individual Problems and Strengths) and RWP (Relationship with Partner) were significantly associated with higher quality of life.ConclusionThe questionnaire could be used in psychotherapy settings for routine outcome monitoring and psychotherapy research.